Using of protective masks after the cancelling of the COVID-19 pandemic restrictions: Prospective cohort research - E. Yu. Pylaeva; D. V. Orlov; N. A. Marudenkov; E. A. Koltsova; M. G. Tataryan; A. A. Litsev; N. N. Zvereva; I. M. Spivak; O. V. Shamsheva; M. A. Sayfullin (LLC "Diagnostics and Vaccines", 2023)
The long-term using of protective masks, linked with the COVID-19 pandemic, could has a significant impact on people from negativism to addiction to use them. Aim: to assess the frequency of mask use after the canceling of restrictions depending on gender and behavioral characteristics, to assess the possible impact of not wearing masks on the incidence of COVID-19. Materials and Methods: We conducted a prospective longitudinal cohort study on the Moscow Metro from 03/15/22 to 04/11/2022. Three cohorts of passengers were identified: K1 - using masks, K2 - wearing masks with defection from rules and K3 - not using masks. The shares of cohorts were determined depending on gender, travel area, time of day, occupation (use of paper information carriers, electronic devices). The proportions, their confidence intervals were determined; the comparison of the significance of differences was carried out using the Pearson chi-square method. Results: we made 28672 observations covering 225 out of 348 metro stations (67.5%). Within 5 weeks (11-15 weeks of 2022 year), the proportion of passengers not using masks (K3) increased from 74% to 94.6%. Starting from the 2nd day, significant differences between men and women were identified. The largest share of K3 passengers was among those using electronic devices. Among those using paper, the trend towards the elimination of masks was the least pronounced. The decrease in passengers using masks in Moscow did not lead to an increase in the incidence of COVID-19. Conclusion: in the absence of legal restrictions, the decision to use masks is influenced by the gender and behavioral characteristics of passengers.